Patogenicidade de isolado de aspergillus westerdijkiae a fêmeas e ootecas de periplaneta americana - Baggio, Mariah Valente [UNESP]; Ferreira, Marcelo Da Costa [UNESP]; Monteiro, Antonio Carlos [UNESP]; Maldonado Junior, Walter [UNESP]; Lemos, Manoel Victor Franco [UNESP] (FapUNIFESP (SciELO), 2016)
Cockroach control is performed by the application of chemical insecticides which exert high selective pressure on populations and introduces synthetic substances in the environment, motivating the search for other methods of control such as entomopathogenic fungi. The objectives of this study were to investigate the pathogenicity of the JAB 42 Aspergillus westerdijkiae to females and oothecae of Periplaneta americana and to demonstrate its mechanism of action on oothecae. Suspensions containing 106 to 108 conidia/ ml were used to infect females and oothecae. Mortality and other variables such as scanning electron microscopy were used to demonstrate the mechanism of action of the fungus. The isolated JAB 42 A. westerdijkiae is pathogenic to oothecae of P. americana, with low capacity to kill females. Adhesion, germination, penetration and extrusion of the fungus on the cockroach oothecae were observed.
Pathogenicity of aspergillus westerdijkiae to females and oothecae of periplaneta americana
Keywords: Biological control; Cockroach; Ovicide